Characterization of enterotoxigenic Bacteroides fragilis by a toxin-specific enzyme-linked immunosorbent assay. - Van Tassell, R L (1994)
Within the past decade, certain strains of Bacteroides fragilis have been associated with diarrhea in humans and cytotoxic activity on certain colon carcinoma cell lines. An enzyme-linked immunosorbent assay (ELISA) for detecting the enterotoxin of B. fragilis in cultures and stools was developed by using high-titer monospecific goat and rabbit antitoxins in an indirect format. The lower limit of detection for purified toxin was approximately 0.05 micrograms/ml; the linear range was from 0.05 to 10 microgram/ml. Using the ELISA to screen cultures of toxigenic and nontoxigenic strains of B. fragilis, we observed 100% correlation with 16 known toxigenic strains which had various cytotoxic activities on HT-29 cells. In addition, we found 6 of 62 previously untested strains also to be positive in both assays. Stability studies revealed that although the cytotoxic activities of crude and purified toxin preparations incubated at elevated temperatures were rapidly lost, the ELISA responses were not significantly reduced. Sodium dodecyl sulfate(SDS)-polyacrylamide gel electrophoresis and SDS-capillary electrophoresis showed that the purified toxin autodigested to several stable peptides. Studies on partially purified membranes from the toxigenic strains revealed the presence of several membrane-associated components which were noncytotoxic but strongly immunoreactive in the ELISA. Preliminary studies with spiked feces indicated that the ELISA may be useful for screening not only cultures for the enterotoxigenic B. fragilis but also stool specimens. Ongoing studies are focusing on determining the nature of the toxin's apparent proteolytic capabilities and investigating the feasibility of using the ELISA on stool specimens from healthy and diarrheic humans.